Ruminations of a Gandhian: Margaret Chatterjee. Issue 2 (December 2016) - Prasad, Sujata
This article is based on conversations the author had with nonagenarian Gandhian, Margaret Chatterjee, over the last one year. It is reflective of Chatterjee's engagement with Gandhian philosophy—non-violence and satyagraha, drawn from influences in Gandhi's life—and captures why she rejects the categorization of Gandhi as either a traditionalist or a modernist.